Postductal Coarctation of Aorta Causing Myocardial Ischaemia and Heart Failure in First Week of Life. Issue 255 (October 1972) - Hallidie-Smith, K. A.
Abstract : Two infants with isolated postductal coarctation of the aorta who developed heart failure in the first week of life are reported. Possible factors contributing to symptomatology from this anomaly in the newborn period are discussed. In these two infants there was some evidence that left ventricular myocardial necrosis was an important factor.